2010
DOI: 10.1128/cvi.00194-10
|View full text |Cite
|
Sign up to set email alerts
|

Serum Intercellular Adhesion Molecule 1 Variations in Young Children with Acute Otitis Media

Abstract: Acute otitis media (AOM) is an inflammatory reaction in the middle ear, most often occurring in young children. Streptococcus pneumoniae, nontypeable Haemophilus influenzae, and Moraxella catarrhalis are the most common bacteria isolated. Intercellular adhesion molecule 1 (ICAM-1) is involved in the innate immune response to infection by microorganisms, in effective antigen presentation, and in subsequent T-cell activation. Here we prospectively studied levels of serum soluble ICAM-1 (sICAM-1) before, at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Closely timed sampling avoided the influence of changing age on responses in pediatric subjects. Our previous work identified significant changes in blood of a limited number of specific pro-inflammatory molecules during AOM caused by Spn [4,5,6]. However, with transcriptome analysis, we were able to identify a much broader range of significant changes in gene regulation.…”
Section: Introductionmentioning
confidence: 73%
“…Closely timed sampling avoided the influence of changing age on responses in pediatric subjects. Our previous work identified significant changes in blood of a limited number of specific pro-inflammatory molecules during AOM caused by Spn [4,5,6]. However, with transcriptome analysis, we were able to identify a much broader range of significant changes in gene regulation.…”
Section: Introductionmentioning
confidence: 73%
“…Thus far, investigators have studied biomarkers in serum and nasopharyngeal secretions and have correlated them with AOM diagnosis, types of bacteria or viruses, and outcome. High serum levels of intercellular adhesion molecule 1 were found in children with AOM compared with healthy children 222 . At the time of AOM onset, the serum levels of S100-A12 were increased, which returned to normal during recovery 223 .…”
Section: Biomarkersmentioning
confidence: 89%
“…In contrast, we did not find significant correlations between both adhesion molecules and any arsenicals in the urine. Prospective cohort studies have reported that the plasma concentration of sICAM-1 is elevated many years before an initial myocardial infarction (Hwang et al 1997; Ridker et al 1998) but sICAM-1 has also been reported to be elevated in children with acute otitis media caused by bacterial infections (Liu et al 2010). In contrast with the adhesion molecules, ADMA was associated with cIMT and with the relative proportion of iAs in our study population.…”
Section: Discussionmentioning
confidence: 99%